(W+2)(w-5)=

Simple and best practice solution for (W+2)(w-5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (W+2)(w-5)= equation:


Simplifying
(W + 2)(w + -5) = 0

Reorder the terms:
(2 + W)(w + -5) = 0

Reorder the terms:
(2 + W)(-5 + w) = 0

Multiply (2 + W) * (-5 + w)
(2(-5 + w) + W(-5 + w)) = 0
((-5 * 2 + w * 2) + W(-5 + w)) = 0
((-10 + 2w) + W(-5 + w)) = 0
(-10 + 2w + (-5 * W + w * W)) = 0
(-10 + 2w + (-5W + wW)) = 0

Reorder the terms:
(-10 + -5W + 2w + wW) = 0
(-10 + -5W + 2w + wW) = 0

Solving
-10 + -5W + 2w + wW = 0

Solving for variable 'W'.

Move all terms containing W to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + -5W + 2w + 10 + wW = 0 + 10

Reorder the terms:
-10 + 10 + -5W + 2w + wW = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -5W + 2w + wW = 0 + 10
-5W + 2w + wW = 0 + 10

Combine like terms: 0 + 10 = 10
-5W + 2w + wW = 10

Add '-2w' to each side of the equation.
-5W + 2w + -2w + wW = 10 + -2w

Combine like terms: 2w + -2w = 0
-5W + 0 + wW = 10 + -2w
-5W + wW = 10 + -2w

Reorder the terms:
-10 + -5W + 2w + wW = 10 + -2w + -10 + 2w

Reorder the terms:
-10 + -5W + 2w + wW = 10 + -10 + -2w + 2w

Combine like terms: 10 + -10 = 0
-10 + -5W + 2w + wW = 0 + -2w + 2w
-10 + -5W + 2w + wW = -2w + 2w

Combine like terms: -2w + 2w = 0
-10 + -5W + 2w + wW = 0

The solution to this equation could not be determined.

See similar equations:

| 2y+10=3y | | 0=2w^2-3w-44 | | 8(-8+8k)=-192 | | 4c-2(x-3)=-2+5x-10 | | 16+8=40 | | 6-6x+5x=13 | | (m-n+k)(m+7n-6k)=0 | | 4(-2+8n)=-136 | | X+2x+7x+9x+1=42 | | 14=21b | | 4(3-2x)=3(2-3x) | | -8=-2n | | -50=5d | | 135=-9k | | 3/4*x=2/7 | | 25x+71=156 | | 4(7x+8)+x=206 | | 2t=lb | | 6r=60 | | 3x+1+58x+33x=115 | | 75s=195 | | 2(-3)+2(-1)-(-3)(-1)+21= | | 3x+1+58x+13x=115 | | x(9+8)=33 | | =11.6 | | Y/3-3=-11 | | 12x+3=3(2x+6) | | 405.36=230+0.64x | | u+6u=14 | | -9+3v=v+3 | | x-3=-3-10x+7x | | -13+5x=x-1 |

Equations solver categories